A Systematic Review of the Sport Psychology Mixed Martial Arts Literature: Replication and Extension - Sydney Cooper; Marc Lochbaum (MDPI AG, 2022)
MMA is a global sport with a growing body of psychological literature. Our main objective was to replicate and extend a past review concerning the sport psychology literature with MMA participants. We conducted our electronic search in EBSCO with the following databases: SPORTDiscus, PsycINFO, ERIC, and Psychology and Behavioral Sciences Collection. Our eligibility criteria were research articles (a) found in academic journals, (b) with MMA participants, and (c) at least one topic found in sport psychology literature. After conducting a PRISMA-guided search, 16 studies met our inclusion criteria. The studies spanned from 2011 to 2021, with 795 MMA participants from the USA (n = 7), Brazil (n = 4), and one study each from Czechia, Poland, Spain, Sweden, and the United Kingdom. From studies reporting mean ages, MMA participants were in their mid-20s (M = 26.55 ± 2.38 years of age). The results section includes risk of bias ratings across five areas (i.e., subject selection, sample's MMA background, participant anonymity, data collection procedures, and questionnaire or qualitative theme reporting). More risk of bias concerns resulted with the quantitative than qualitative articles. To best represent the studies, we presented separate results tables with many specifics for both the quantitative (i.e., topic, main analysis, time frame, summary of results, and meaningfulness) and qualitative studies (topic, main analysis, time frame, and main themes). The included studies covered a variety of historic and meta-analyzed topics such as confidence, mood, motivations, and social facilitation. Based on our review, we discussed the literature strengths and limitations, and suggested future research directions. Last, we provided practical points for both MMA participants and their trainers.